2020
DOI: 10.1186/s12889-020-08700-x
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco use: its prevalence and relationships with dental symptoms, nutritional status and blood pressure among rural women in Burkina Faso

Abstract: Background: Sub-Saharan women use smokeless tobacco (SLT) more than smoked tobacco. Among Western African countries, the estimated weighted prevalence of SLT use in rural women was found to be the highest in Burkina Faso (after Sierra Leone). This study aimed to assess the prevalence of SLT use and its associated factors among rural women in Burkina Faso by using nationally representative data. Methods: We used data from the 2013 STEPwise approach to Surveillance (STEPS) study, which provided sociodemographic,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Consistent with previous study findings [ 30 ], in this study, we did not find a significant difference in the prevalence of the co-occurrence of two or more risk factors between rural and urban areas. This finding might be explained by the fact that, in rural areas, many women engage in smokeless tobacco use (which was included in this study to define tobacco used) [ 23 , 31 ]. In addition, low fruit and vegetable consumption and alcohol consumption are also prevalent in rural areas [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous study findings [ 30 ], in this study, we did not find a significant difference in the prevalence of the co-occurrence of two or more risk factors between rural and urban areas. This finding might be explained by the fact that, in rural areas, many women engage in smokeless tobacco use (which was included in this study to define tobacco used) [ 23 , 31 ]. In addition, low fruit and vegetable consumption and alcohol consumption are also prevalent in rural areas [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with reported trends that indicated that the use of non-cigarette forms of tobacco was increasing among women [ 14 , 15 , 16 , 17 ]. Likewise, in Burkina Faso, it was observed that women prefer to use chewable smokeless tobacco, an act which is socially permissive [ 18 ]. While the trends of SLT use in Uganda mirror those in South and Southeast Asian nations, the cultural alignment and acceptance of SLT use for women is different and warrants deeper research.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because the practice of chewing tobacco is a cultural behavior in the study area. Several studies have indicated an association between tobacco use and high blood pressure [55].…”
Section: Data Quality and Validitymentioning
confidence: 99%